Commodities as an Asset Class Essays on Inflation, the Paradox of Gold and the Impact of Crypto - Futerman, Alan G.; Sarjanovic, Ivo A. (Palgrave Studies in Classical Liberalism, 2022)
XXXIII, 161 p. 114 illus., 113 illus. in color.